2021
DOI: 10.3390/en14051477
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Municipal Sewage Sludge to Investigate Char and Phosphorous Yield together with Heavy-Metal Removal—Experimental and by Thermodynamic Calculations

Abstract: Sewage sludge is regarded as a potential source for soil fertilizer However, the direct utilization of sewage sludge in agricultural land is restricted since it also contains heavy metals, pathogens, and toxic compounds. Pyrolysis of the sewage sludge destroys the organic pollutants and partly volatilizes the heavy metals. In this study, pyrolysis of sewage sludge was carried out in order to determine the optimum residence time and temperature to recover the phosphorous and remove heavy metals from the resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Based on these results, it appears that there is the potential to use pyrolysis as an effective means of recovering and reusing both the energy and phosphorus present in SS [89]. Vali et al [142] showed that over 90% of the phosphorus contained in SS was retained in the char after pyrolysis at temperatures up to 850 • C, while higher temperature led to the formation of gaseous P compounds. At the same time, the concentration of HMs in the char decreased significantly (except Cu and Zn), as most of them were volatilized in the gas phase or solubilized into the aqueous phase.…”
Section: Pyrolysis and Gasificationmentioning
confidence: 99%
“…Based on these results, it appears that there is the potential to use pyrolysis as an effective means of recovering and reusing both the energy and phosphorus present in SS [89]. Vali et al [142] showed that over 90% of the phosphorus contained in SS was retained in the char after pyrolysis at temperatures up to 850 • C, while higher temperature led to the formation of gaseous P compounds. At the same time, the concentration of HMs in the char decreased significantly (except Cu and Zn), as most of them were volatilized in the gas phase or solubilized into the aqueous phase.…”
Section: Pyrolysis and Gasificationmentioning
confidence: 99%
“…e effect of pyrolysis temperature on the concentration of trace metals in the biochars was the main focus of research on the production and characterization of biochars [11]. However, the toxicity of the produced biochar is still unclear [41]. In this study, a phytotoxicity test is used as an effective and a low-cost equipment to identify the toxic effects of the produced biochars on root elongation inhibition (REI) of lettuce seeds (Figure 2).…”
Section: Effect Of Pyrolysis Temperature On Trace Metal Concentration and Biochar Toxicitymentioning
confidence: 99%
“…Recently, it was demonstrated that SS pyrolysis can cause the thermal breakdown of pathogens and some toxic organic compounds [38,39], required for possible land application [40,41]. Consequently, biochar derived from SS can have a significant impact on the physical, chemical, and biological properties of depleted soils without posing a risk of contamination [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on conditions of pyrolysis and type of SS [15], biochars obtained from SS pyrolysis are highly macroporous, with the small volumes of the meso-and micro-pores [19] among others, e.g., wood-derived biochar. However, one should bear in mind that the pyrolysis conditions regulate the availability and toxicity of emerging contaminants [20,21]. For instance, it has been reported that, pyrolysis at lower temperature of 300 °C resulted in the significant reduction in DTPA (diethylenetriaminepentaacetic acid)-extractable metals in the SS-derived biochar [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased temperature led to increased content of stable aromatic carbon, ash, some macro-(Ca, Mg, P, and K) and micronutrients (Cu and Zn) and increased alkali reaction [20]. Nevertheless, a suitable temperature of the SS pyrolysis can be used to transform bioavailable heavy metals into less soluble forms [21,23].…”
Section: Introductionmentioning
confidence: 99%